How accurate are A-REIT IPO dividend forecasts?. Issue 1 (6th November 2019) - Dimovski, Bill; Ratcliffe, Rebecca; Ratcliffe, Christopher; Keneley, Monica; Salzman, Scott
Abstract : Purpose: The purpose of this paper is to investigate the accuracy of Australian Real Estate Investment Trust (A-REIT) initial public offering (IPO) dividend forecasts between 1994 and 2016. Design/methodology/approach: This study compares the dividend forecasts of A-REIT IPOs for the first dividend forecast period in the prospectus, with the actual dividend declared for that forecast period. As well as simple descriptive summary measures, this study also employs an exact logistic regression approach to examine the factors that might influence the IPOs achieving or exceeding the dividend forecast. Findings: The study identifies that the dividends declared, on average, were greater than the dividend forecast and that more than nine out of ten of the IPOs listed after 1999 achieved or exceeded their prospectus forecast. In addition the authors observe positive mean forecast errors, suggesting dividend forecasts in A-REIT IPOs, are cautiously biased. This is in contrast to the industrial company data reported in Brown et al. (2000) which suggest dividend forecasts are optimistically biased. The study also finds the A-REIT IPOs that did not forecast a dividend, generally did not pay a dividend. Practical implications: The results will inform dividend seeking institutional and retail investors of the investment opportunities in A-REIT IPOs. Originality/value: This paper adds to the discussion of the relative predictability of dividends of A-REIT IPOs compared to industrial company IPOs.